Preliminary study on decision making factors to replace medical equipment in hospital - Salim, Siti Hajar; Mazlan, Saiful Amri; Salim, Siti Aisyah (Penerbit UTHM, 2019)
Maintaining medical equipment in hospital is a cost-deprived process yet is a crucial process that needs to be looked into. Maintaining is an ongoing process that starts with installation and ended up with disposed. The cost for maintaining equipment is often held a large portion in life cycle costing and huge amount of money need to be allocated to complete this process. The cost invested on maintaining the medical equipment should be worth the value without comprising the safety requirement and regulations. However, there are circumstances where hospitals are unable to decide when to dispose the equipment especially when the equipment reach the end of its life, incur high repairing cost, aging, and frequent failed to function. Management of hospital come into dead end solution as there are lack of proper guidelines on maintaining medical equipment and therefore the equipment may be over maintained or under maintained. This paper provides a review of 100 papers from credible sources on maintaining activities of equipment to identify factors that are important for decision making to replace the medical equipment.